Invasive mutualisms between a plant pathogen and insect vectors in the Middle East and Brazil. Issue 12 (December 2016) - Queiroz, Renan Batista; Donkersley, Philip; Silva, Fábio Nascimento; Al-Mahmmoli, Issa Hashil; Al-Sadi, Abdullah Mohammed; Carvalho, Claudine Márcia; Elliot, Simon L.
Abstract : Complex multi-trophic interactions in vectorborne diseases limit our understanding and ability to predict outbreaks. Arthropod-vectored pathogens are especially problematic, with the potential for novel interspecific interactions during invasions. Variations and novelties in plant–arthropod–pathogen triumvirates present significant threats to global food security. We examined aspects of a phytoplasma pathogen of citrus across two continents. ' Candidatus Phytoplasma aurantifolia' causes Witches' Broom Disease of Lime (WBDL) and has devastated citrus production in the Middle East. A variant of this phytoplasma currently displays asymptomatic or 'silent' infections in Brazil. We first studied vector capacity and fitness impacts of the pathogen on its vectors. The potential for co-occurring weed species to act as pathogen reservoirs was analysed and key transmission periods in the year were also studied. We demonstrate that two invasive hemipteran insects— Diaphorina citri and Hishimonus phycitis —can vector the phytoplasma. Feeding on phytoplasma-infected hosts greatly increased reproduction of its invasive vector D. citri both in Oman and Brazil; suggesting that increased fitness of invasive insect vectors thereby further increases the pathogen's capacity to spread. Based on our findings, this is a robust system for studying the effects of invasions on vectorborne diseases and highlights concerns about its spread to warmer, drier regions of Brazil.